Combination of Autophagy Selective Therapeutics With Doxil: An Assessment of Pathological Toxicity - Helke, Kristi L.; Gudi, Radhika R.; Vasu, Chenthamarakshan; Delaney, Joe R. (Frontiers in Toxicology, 2022)
Background. Combination therapy of targeted drugs in cancer treatment is a field in constant flux, with research balancing side effects with efficacy. Efficacy from combination therapy is improved either through synthetic lethality or through prevention of recurrent clones. Previous research has shown (hydroxy-)chloroquine is insufficient to disrupt autophagy in tumors. Hence, either combinations or novel autophagy agents are desired. In vivo studies of ovarian cancer have revealed that chloroquine can be combined with up to four other autophagy drugs to suppress ovarian cancer growth. While cancer efficacy is now established for the autophagy drug combination, it is unclear what toxicities may require monitoring in human trials. Additive toxicity with chemotherapy is also unknown. Methods. To address toxicity in more depth than previous weight-monitoring studies, biochemical and histopathology studies were performed. Mouse groups were treated with autophagy drugs for two weeks, with or without the chemotherapy Doxil. After the last dose, mice were processed for blood biochemistry, white blood cell markers, and histopathology. Results. Data from a comprehensive blood biochemistry panel, flow cytometric measurements of blood cell markers, and histopathology are herein reported. While Doxil presented clear bone marrow and immunologic toxicity, autophagy drugs were overall less toxic and more variable in their presentation of potential toxicities. Only minor additive effects of autophagy drugs with Doxil were observed. Conclusion. Combinations of autophagy drugs may be considered for therapy in human oncology trials, with possible side effects to monitor informed by these murine pre-clinical data.